Protótipo de um sistema de informação para gestão pública integrada de resíduos sólidos urbanos - Rollwagen, André Fernando (2013)
The production of municipal solid waste has grown considerably in recent decades, mainly due to population growth and consumption of industrial products, which creates social, economic and environmental problems. Considering the lack of a computerized information system, the management of such waste occurs through disjointed and inaccurate actions. The aim of this research is to present the analysis and design of an integrated information system for public management of urban solid waste to medium size municipalities. The methodology included: investigation of the current structure of public management of urban solid waste in Passo Fundo; requirements elicitation and the analysis and computerized information system design. This model allows the recording of data, reporting and performance indicators, storing date information seamlessly. We intent, therefore, the possibility of improvements in public management of urban solid waste, bringing advancements like organization and bringing greater reliability to the process